Unraveling the hidden paleobiodiversity of the Middle Devonian (Emsian) crinoids (Crinoidea, Echinodermata) from Poland - William I. Ausich; Mariusz A. Salamon; Bartosz J. Płachno; Tomasz Brachaniec; Wojciech Krawczyński; Andrzej Boczarowski; Karolina Paszcza; Magdalena Łukowiak; Przemysław Gorzelak (PeerJ, 2022)
Most previous publications on Devonian crinoids from the Holy Cross Mountains in Poland have concentrated on crinoid columns, and until now, little has been published about crinoid cups and calyxes. Herein, five crinoid taxa are described from an abundant occurrence of aboral cups and partial crowns from the Bukowa Góra Member (Emsian) in the Holy Cross Mountains of southern Poland. The following taxa are described: Bactrocrinites sp., Codiacrinus sevastopuloi sp. nov., Halocrinites geminatus (Bohatý, 2005), Halocrinites schlotheimii Steininger, 1831, and a single brachial plate from a flexible crinoid placed in Flexibilia incertae sedis. Simple discoid holdfasts are also present encrusted to cylindrical stromatoporoids. These taxa are the first crinoids described from the remains of partial crowns from Emsian strata of Poland.